2010
DOI: 10.1167/iovs.09-4921
|View full text |Cite
|
Sign up to set email alerts
|

Effect of TIMP-1 and MMP in Pterygium Invasion

Abstract: PURPOSE. The migration and invasion of tumor cells correlate with the interaction between MMP and TIMP. Therefore, the purpose of this study was to determine the role of MMP-9, MMP-10, and TIMPs in pterygium formation and progression. METHODS. MMP-9, MMP-10, and TIMP proteins were studied using immunohistochemistry on 82 pterygial specimens and 30 normal conjunctivas. Pterygium epithelial cells (PECs), cultured in a serum-free culture medium, and siRNA were used to knock down TIMP gene expression to understand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
44
2
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(49 citation statements)
references
References 16 publications
2
44
2
1
Order By: Relevance
“…12 MMPs inhibitors (TIMPs) have been found with high expression in pterygium samples; along with the high levels of MMPs, these proteins may be active participants in the extensive matrix turnover and infiltration that characterize pterygium. 4 The expression levels of these proteinases and their inhibitors could mediate the velocity of pterygium formation and expansion.…”
Section: Extracellular Matrix Modulatorsmentioning
confidence: 99%
See 2 more Smart Citations
“…12 MMPs inhibitors (TIMPs) have been found with high expression in pterygium samples; along with the high levels of MMPs, these proteins may be active participants in the extensive matrix turnover and infiltration that characterize pterygium. 4 The expression levels of these proteinases and their inhibitors could mediate the velocity of pterygium formation and expansion.…”
Section: Extracellular Matrix Modulatorsmentioning
confidence: 99%
“…It is characterized by an altered basal epithelial cell proliferation, vascularization, and invasion of the adjacent corneal epithelium. [1][2][3][4][5] The progression of this disease first involves the presence of gray circumscribed dots in the cornea near the limbus, with simultaneous tense conjunctiva that appear opposite to the area of corneal affection, and there is also displacement of the plica. Later, a wing-shaped extension of the fleshy growth of the bulbar conjunctiva onto the cornea takes place.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While Tsai et al [23] found practically little or no expression of these species, Yang et al [24] found both MMP-2 and MMP-9 activities in normal tissue. In these cases, pathology was related to higher expression and/or activity of the tested MMPs.…”
Section: Discussionmentioning
confidence: 97%
“…Also, in early-stage pterygium tissues and cultured fibroblasts, MMP-2 or MMP-9 was at low or undetectable levels, while in advanced-stage pterygium (pterygium head passed the papillary region), MMP-2 and MMP-9 could be obviously detected in pterygium tissues and fibroblasts (16). In addition, down-regulation of the expression levels of MMP-3 and MMP-13 was capable of suppression of the proliferation and migration of pterygium fibroblasts (24,25). These findings support the idea that MMPs may play an important role in the progression of pterygium, and the genomic markers on MMPs can serve as valuable predictive biomarkers for the development or reoccurrence of pterygium.…”
Section: Discussionmentioning
confidence: 98%